Educational Games in Education of Communication Culture of Pre-School Children - Boyborieva Saodat (Indonesian Journal of Innovation Studies, 2022)
The article deals with some issues of teaching children to think independently through didactic games in speech development classes in preschool education, and expresses theoretical views.